Design to stimulate territorial experiences with art - Tonetto, Leandro Miletto; Tarouco, Fabrício Farias; Greggianin, Monica (Pós. Revista do Programa de Pós-Graduação em Arquitetura e Urbanismo da FAUUSP, 2015)
Porto Alegre, capital city of the state of Rio Grande do Sul, promotes itself as cultural destination for the local community, as well as for visitors. Some of its most popular projects are Porto Alegre em Cena, Porto Verão Alegre, Serenata Iluminada, and the Mercosul Biennial of Visual Arts, which had its ninth edition in 2013. In this context, this study investigates how we can design stimuli that encourage citizens to establish connections with art in the city of Porto Alegre, building on the experience of the 9th Mercosul Biennial. We have made use of 20 indepth exploratory interviews with individuals who had visited the Mercosul Biennial several times. We have discussed the findings based on their potential to foster territorial design projects able to ratify the city’s potential to stimulate the connection between people and art, which can be developed by various institutions through planned interventions. Moreover, we have observed that the territory, as a design object, can provide not only a suitable place for people to dwell, but also facilitate social dynamics that happen in that territory. In this setting, the interaction between territory, art, and people encourages the strengthening of emotional bonds between the Mercosul Biennial and the city. As a metropolis permeated with art during the period of the Mercosul Biennial, Porto Alegre represents a unique noteworthy phenomenon. The conclusion suggests that in spite of the fact that some elements appear to be independent of the city, others, such as the use of the city’s characteristic areas, are clearly circumscribed to local aspects.